2019
DOI: 10.1098/rsos.190866
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ether- block -amide) copolymer membrane for CO 2 /N 2 separation: the influence of the casting solution concentration on its morphology, thermal properties and gas separation performance

Abstract: The present work is focused on the study of the effect that the casting solution concentration has on the morphology and gas separation performance of poly(ether- block -amide) copolymer membranes (Pebax ® MH 1657). With this aim, three different concentrations of Pebax ® MH 1657 in the casting solution (1, 3 and 5 wt%) were used to prepare dense membranes with a thickness of 40 µm. The morphology and thermal stability of all membranes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
6
37
0
Order By: Relevance
“…Moving to 9 wt% Pebax MH 1657, it was found that selectivity this bare membrane decreased significantly compared to 6 wt% bare membrane (see Figure 7 and Table 4). This trend is also reported by Martínez-Izquierdo et al [31] The highest CO 2 / N 2 selectivity of 36 ± 7 and the permeability of 137 ± 31 Barrer were obtained for 9 wt% Pebax MH 1657 based MMMs and 10 wt% loading of ZIF-94 (1). Comparison with bare membrane indicates that 10 wt% ZIF-94 (1) dose in the MMM increases selectivity and permeability by 71% and 80%, respectively.…”
Section: Mmms Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…Moving to 9 wt% Pebax MH 1657, it was found that selectivity this bare membrane decreased significantly compared to 6 wt% bare membrane (see Figure 7 and Table 4). This trend is also reported by Martínez-Izquierdo et al [31] The highest CO 2 / N 2 selectivity of 36 ± 7 and the permeability of 137 ± 31 Barrer were obtained for 9 wt% Pebax MH 1657 based MMMs and 10 wt% loading of ZIF-94 (1). Comparison with bare membrane indicates that 10 wt% ZIF-94 (1) dose in the MMM increases selectivity and permeability by 71% and 80%, respectively.…”
Section: Mmms Performancesupporting
confidence: 86%
“…The MMMs were prepared following a two-step process. [31] First, 6 and 9 wt% Pebax MH 1657 (of total weight of 3 g (polymer + solvent)) was dissolved in EtOH/ water (70/30 (v/v)) by stirring under reflux for 1 h. Afterward, the dissolved polymer was used to cast bare polymeric membranes. In case of MMMs fabrication process, ZIF-94 was dispersed in the dissolved polymer.…”
Section: Fabrication Of Mmmsmentioning
confidence: 99%
“…The results indicate that the developed MMMs could be a potential candidate for CO 2 separation applications. The separation performance of CO 2 /N 2 lies on the 2008 upper bound and is better than that of pristine Pebax [44,[50][51][52], various Pebax-based MMMs [46,50,[52][53][54][55][56], and commercial polymers, including CA [57,58], Matrimid [18,59], etc.…”
Section: Permeability Vs Selectivity Of the Pim-g-mof-xmentioning
confidence: 99%
“…6 Our research group published recently the influence of the casting solution concentration in the preparation of Pebax ® 1657 membranes, showing a gas separation performance of 100 Barrer of CO2 with a CO2/N2 selectivity of 35. 7 Khosravi et. al.…”
Section: Introductionmentioning
confidence: 99%